The Influencing Factor of the Student Behavioral Intention in Garbage Managementat Nursing Academy and Midwifery Academy in Pematangsiantar - Lismawati, Lismawati; Utama, Indra; Asnawati, Seri; Purba, Wulan Sari (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Background: The increasing population will influence the number of garbage. A pile of garbageincreases as many as 4% in every year, and in Sumatra has 8.7 billion ton a pile of garbage. The way to minimize the garbages by the managing or recycling. Aim: To comprehend the student in garbage managingat Pematangsiantar. Method: This study used cross-sectional with 228 students as a sample. Result: 53.3% of the respondent has a high behavioral intentionin garbage-managing with used the garbage in another time, while as many as 52.2% has a behavioral control, and subjective norm by the respondent be a high result of three-point in the analysis, represented with 72.4%. The effect of bivariate analysis found that behavior, subjective norm, and behavioral controlrelatedtothe behavior of student intention.Conclusion: This study showed that there is a correlation between behavior, subjective norm, andbehavioral control with behavior intention. The wishes ofthe student to caring formanaging or recycling because the garbage has many effectson the environment.